1996
DOI: 10.1002/(sici)1097-0010(199611)72:3<306::aid-jsfa659>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Ethylene in the Regulation of Fruit Ripening in the Hillawi Date Palm (Phoenix dactyliferaL)

Abstract: The role of ethylene in the regulation of fruit ripening in the date palm (Phoenix dactyliferaL) was investigated. It was found that the rate of CO2 output was high initially, but the rate declined steadily as the fruit advanced in maturity, reaching its lowest level as the fruit entered the stage of physiological maturity, but then the rate of respiration increased as the fruit entered the ripening phase, reached a peak value and then declined. Ethylene emission was not detected until the 91st day from pollin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 8 publications
1
18
0
Order By: Relevance
“…9 Changes in chemical composition, ie total soluble solids, titratable acidity, protein and sugars (invertase was inactivated by plunging the fresh samples into boiling ethanol during preliminary extraction), were measured using the methods of the AOAC, 10 unless stated otherwise. A completely randomised design was used with four replicates (each replicate consisted of at least 30-50 fruits, depending on the stage of maturity).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Changes in chemical composition, ie total soluble solids, titratable acidity, protein and sugars (invertase was inactivated by plunging the fresh samples into boiling ethanol during preliminary extraction), were measured using the methods of the AOAC, 10 unless stated otherwise. A completely randomised design was used with four replicates (each replicate consisted of at least 30-50 fruits, depending on the stage of maturity).…”
Section: Methodsmentioning
confidence: 99%
“…17 However, for date palm fruit (Phoenix dactylifera L) it was found that the peak of ethylene production preceded the climacteric peak by 7 days. 9 During the second period of rapid growth the rate of respiration increased sevenfold, whilst the rate of ethylene production increased 47-fold. The rate of ethylene production by ripe jujube fruit cv Zaytoni is considered very high according to the classification of Kader and Kasmire.…”
Section: Respiration Rate and Ethylene Productionmentioning
confidence: 99%
“…The normal date palm fruit is a berry which results from the ovary (Mater, 1991). After pollination and fertilization, fruit growth follows a sigmoidal curve, and is usually divided into fi ve stages of development known by their Arabic terms: 'hababouk', 'kimri' (kimri, jimri), 'khalal' (balah, bisr), 'rutab' and 'tamr' (tamar) ( Figure 4.2 ) (Abbas and Ibrahim, 1996;Ait-Oubahou and Yahia, 1999;Yahia, 2004). The 'hababouk' stage starts after fertilization and is characterized by the loss of two unfertilized carpels.…”
Section: Fruit Growth Patternmentioning
confidence: 99%
“…Cured Deglet Noor dates with 20-22% moisture produced 0.4 mg CO 2 kg −1 h −1 at 24°C, and 2 mg CO 2 kg −1 h −1 when the moisture content increased to 27% (Rygg, 1975). The rate of CO 2 production is high initially, but declines steadily as the fruit advances in maturity, reaching its lowest level as the fruit enters the stage of physiological maturity, and then increases to reach a peak as the fruit ripens (Abbas and Ibrahim, 1996). Rouhani and Bassiri (1976) found that the respiration rate of Shahani dates was high during the early stages of fruit development and decreased sharply as the fruit entered the ripening phase.…”
Section: Respirationmentioning
confidence: 99%
See 1 more Smart Citation